Judicialization of nursing malpractice in perioperative care, and delivery and birth assistance - Gislene Aparecida Xavier dos Reis; Laura Misue Matsuda; Verusca Soares de Souza; Andressa Martins Dias Ferreira; João Lucas Campos de Oliveira; Maria Antonia Ramos Costa; Kelly Cristina Inoue (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the legal outcomes of malpractices in perioperative care, and delivery and birth assistance related to nursing, from the perspective of legal support for malpractice prevention. Methods: an exploratory, documentary, qualitative study, based on the cases tried by the Court of Justice of the State of Paraná, available online until April 2018. For the data analysis, we codified the processes and summarized the judicial outcome by the severity of the malpractice. Then, we recommended practices for the prevention of each case we presented. Results: among the thirteen processes analyzed, eight corresponded to the perioperative period (mainly electrocautery burn), and five to nursing care for delivery and birth. The severity of the cases was high (n=7). The judicial outcome of most cases (n=11) was the conviction of the institution. Conclusions: despite the multifactorial nature of the malpractices, the identified ones are preventable since there is a description of good practices.